Comprehensive Broiler Supply Chain Model with Vertical and Horizontal Linkages: Impact of US–China Trade War and USMCA. (31st August 2020) - Unveren, Hakan; Luckstead, Jeff
Abstract: This paper builds a comprehensive supply chain model of the US broiler industry that accounts for corn and soybean meal, feed mills, breeders, hatcheries, grow-out farms, broiler processing, value-added processing, and international trade. The model is calibrated and simulated to analyze the effects of (1) corn and soybeans tariffs imposed by China and (2) change in the Canadian tariff-rate quota proposed under US–Mexico–Canada–Agreement. The first scenario indicates that feed price falls while supply increases, which decreases the production costs of breeders and grow-out farms. The second scenario shows that exports to Canada rise at the expense of exports to Mexico.